Analisis Beban Kerja untuk Menetapkan Kebijakan SDM tentang Pengaturan Beban Kerja pada Karyawan Admin Bagian Logistik PT XUPN - Satrio Wicaksono, (2021)
PT X is a company engaged in distribution and trading as its business activities. The logistics division, especially the logistics admin as a supply chain, certainly has a big responsibility. In order to carry out this great responsibility, an appropriate number of workers is needed so that the work carried out can be carried out properly. In this study, the main objective is to analyze the workload that exists in the current logistics admin employees and later from the results of the workload analysis, a human resource policy can be drawn about workload regulation. The method used in this study is the Full Time Equivalent (FTE) method where this method can show how much workload is proportional to each employee. As a result, the workload received by each logistics admin employee has a different workload from one employee to another. Of the three existing logistics admin employees, 2 are overloaded and one is inloaded. Human resource policies related to workload arrangements for logistics admin employees of PT X can be said to have not been maximized due to differences in workloads for each employee even though each of them does the same job.